The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3997/2214-4609.20144387
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Monitoring of Simulated Clandestine Graves Using Electrical and GPR Methods - 0-3 Years after Burial

Abstract: SummaryThis study provides forensic search teams with systematic geophysical monitoring data over simulated clandestine graves for comparison to active cases. Simulated 'wrapped' and 'naked' burials were created. Multi-geophysical surveys were collected over a three-year monitoring period. Bulk ground resistivity, Electrical Resistivity Imaging, multi-frequency Ground Penetrating Radar and grave 'soil water' conductivity data were collected. Resistivity surveys revealed the naked burial had consistently low-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…These have been repeatedly geophysically surveyed by fixed-offset electrical and Electrical Resistivity Imaging (ERI) surveys as well as multi-frequency (110-900 MHz) GPR datasets at least quarterly, and every month in the first three years post-burial. Studies have been published on determining what causes relative resistivity anomalies [19], magnetic surveys [20], measurements of decompositional fluid conductivities over time [3] as well as the 0-3 years post-burial datasets [6]. Repeat surveys suggest winter surveys are optimal and resistivity surveys should be undertaken six months to two years post-burial for optimal success.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These have been repeatedly geophysically surveyed by fixed-offset electrical and Electrical Resistivity Imaging (ERI) surveys as well as multi-frequency (110-900 MHz) GPR datasets at least quarterly, and every month in the first three years post-burial. Studies have been published on determining what causes relative resistivity anomalies [19], magnetic surveys [20], measurements of decompositional fluid conductivities over time [3] as well as the 0-3 years post-burial datasets [6]. Repeat surveys suggest winter surveys are optimal and resistivity surveys should be undertaken six months to two years post-burial for optimal success.…”
Section: Introductionmentioning
confidence: 99%
“…Geoscientific methods are being increasingly utilised by forensic search teams for the detection and location of clandestinely buried material [4][5]. In the search for clandestine graves of murder victims, burials are usually shallow (less than 3 m and typically 0.5 m below ground level or bgl [6]), but current detection rates are low and, without locating the victim's body, obtaining a successful conviction can be very difficult [1,2]. Search investigators will use a variety of proved methods, which include scenariobased, feature focused, intelligence-led and systematic Standard Operating Procedures [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into better forensic techniques with GPR has been continually undertaken in recent years with the use of simulated burial and pig cadavers as these are similar in the way they decompose to humans (see, e.g. [6,8,9]). …”
Section: Introductionmentioning
confidence: 99%
“…[3][4] and for human remains (e.g. [3,[5][6][7][8][9]). [10] conducted a control study with buried weapons and found that electro-magnetic equipment could detect metallic objects buried in a grid distribution in a rural environment.…”
Section: Introductionmentioning
confidence: 99%